2014
DOI: 10.4149/av_2014_03_223
|View full text |Cite
|
Sign up to set email alerts
|

Different outcomes of infection of chickens and ducks with a duck-origin H9N2 influenza A virus

Abstract: Summary. -As the major aquatic and terrestrial hosts for avian influenza viruses (AIVs), ducks and chickens play a critical role in the evolution and spread of the H9N2 virus. However, the outcomes of infection of ducks and chickens with the H9N2 virus are not sufficiently documented. In this study, we compared the outcomes of infection of chickens and Peking ducks with a duck-origin H9N2 virus. The results showed that this virus caused more pronounced clinical signs and histological lesions in chickens. As fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…All these results indicate that the H9N2 AIVs do not replicate efficiently in ducks, and are consistent with previous studies in ducks and chickens [ 11 , 12 ]. Wang et al reported that the virus could be detected in the oropharyngeal swabs collected from the ducks that were intranasally infected with 10 7 EID 50 of different H9N2 AIVs at 2 and 3 dpi [ 11 ]. Only a small proportion of inoculated chickens shed detectable viruses found in the cloacal swabs after intranasal infection with chicken origin H9N2 viruses [ 12 ].…”
Section: Resultssupporting
confidence: 93%
“…All these results indicate that the H9N2 AIVs do not replicate efficiently in ducks, and are consistent with previous studies in ducks and chickens [ 11 , 12 ]. Wang et al reported that the virus could be detected in the oropharyngeal swabs collected from the ducks that were intranasally infected with 10 7 EID 50 of different H9N2 AIVs at 2 and 3 dpi [ 11 ]. Only a small proportion of inoculated chickens shed detectable viruses found in the cloacal swabs after intranasal infection with chicken origin H9N2 viruses [ 12 ].…”
Section: Resultssupporting
confidence: 93%
“…Turkeys are one of the most susceptible avian species showing considerable morbidity and mortality (Homme and Easterday 1970). Furthermore, high H9N2 virus isolation rates from apparently healthy chickens, ducks, and other minor poultry species (such as quail, partridges, chukar, pheasant, and guinea fowl) in live poultry markets have been reported (Xu et al 2007b;Wang et al 2014Wang et al , 2015b. Interestingly, H9N2 viruses are frequently found in coinfections with H5N1 HPAI viruses in poultry flocks in Egypt in apparently healthy birds (Arafa et al 2012;Monne et al 2013;Naguib et al 2017).…”
Section: Clinical Signs Pathology and Interspecies Transmissionmentioning
confidence: 99%
“…Similarly, IL-6 and IL-8 were highly upregulated in chickens infected with (A/turkey/England/50-92/91, H5N1-tyEng91) or (A/ turkey/Turkey/1/05, H5N1-tyTR05), but these cytokines were unchanged in infected ducks (Kuchipudi et al, 2014). Previous studies have showed that the expression of IL-6 was associated with the pathogen damage to the organs of host and the replication of virus in organs (Karpala et al, 2011;Wang et al, 2014). Here, moderated expression of IL-6 and IL-8 was seen in the two groups of inoculated ducks at 12 HPI and 3 DPI, but significantly higher expression was observed in the DK87-inoculated ducks at 3 DPI (p < 0.05).…”
Section: Discussionmentioning
confidence: 93%